Delik katerlerinin serlik değişiminin kesme esnasında titreşime etkileri - Kayaş, Akif (My University, 2010)
SYNTHESIS AND CHARACTERIZATION OF PERIPHERALLY AND NONPERIPHERALLY 7-OXY-3-[2-NITRO-4-(TRIFLUORO METHYL)PHENYL]COUMARIN SUBSTITUTED PHTHALO-CYANINES Coumarin (2H-l-benzopyran-2-one) and its derivatives occur widely in nature. The coumarins belong to a group of compounds known as benzopyrones, all of which consist of a benzen ring joined to a pyrone. Many natural and synthetic derivatives of coumarin are used in different applications in chemistry, biology, medicine and physics, including additives in food and cosmetics, optical brightening agents, dispersed fluorescent and laser dyes, in the preparation of insecticides. On the other hand, the diverse biological activities of coumarins are well known as anticoagulant, antithrombotic, antimicrobial, antibacterial, anticancer and anti-HIV activities. For this reason, considerable attention has been paid to the preparation of coumarin derivatives substituted at different positions and their spectral characteristics have been studied. Phthalocyanines form an important class of macrocyclic compounds that do not occur in nature. These macrocyclics are blue and green 18 π-electron conjugated compounds which have found application as dyes and pigments. The compound and its metal derivatives have been studied very extensively since its first discovery in 1907 as a by-product in the synthesis of o-cyanobenzamide. A major disadvantage of phthalocyanines and metallophthalocyanines are their low solubility in organic solvents or water. Their solubility can be improved by the incorporation of substituents, such as alkyl or alkoxy groups of different chain lengths, or branched systems at peripheral positions. In view of the biological importance of both coumarins and Pcs it is worthwhile to combine these two functional molecules into a single compound via synthetic methodology and prepare and characterize their metal-free and metallo derivatives, which may also exhibit biological activities. In this study, phthalocyanines with four peripheral and nonperipheral 7-oxy-3-[2-nitro-3-(trifluoromethyl)phenyl]coumarin substituents were prepared and their complexes with Zn (II), Co (II) metal salts investigated. All of the phthalocyanines were purified by washing with different organic solvents. Novel compounds were characterized by UV-Vis, FT-IR, MS spectroscopies.

THE AFFECT OF THE BORING BARS HARDNESS CHANGE ON THE VIBRATION DURING CUTTING OPERATION Today many in the industry, particularly in the automotive industry the AISI 4140 steel parts are using. Because of, good mechanical properties and easy supply, increase the field of these steels. Parts thats manufaturing from AISI 4140 various problems occur during machining processing. During drilling of holes, occuring unwanted roughness on the turning surfaces with effect of vibration. To investigate the effects of vibration to be done in parallel with these studies hardness tool holder holes examined the effects of ideal hardness values are determined, the operation of turning out of control because of vibrations, depending on it, the surface roughness of uncertainty is under control will allow. Experimental design techniques brings significant advantages to engineering works. Detailed study of this approach were made from AISI 4340 holes in three different hardness samples taken at tool holder performance optimization are investigated. Targeted to reach the optimum point in industrial environments, which are the most important factor tool holder hardness, the effect of cutting speed and feed rate with the help of the Taguchi experimental design techniques were investigated. Evaluation of experimental results variance analysis and signal / noise ratio used in the experiments can be made according to the Taguchi l9 vertical layout. In a full factorial design of experiments with only one of three of the required number of experiments (27 instead of 9 experiments) has been possible to achieve the targeted results.
Keywords: Makine Eğitimi